Rancang Bangun Aplikasi Pengolahan Data Pakan Ternak Berbasis Web pada PT. Baling-Baling Bambu Sumbawa - Shinta Essabella; Rahmad Guswandi; Fatihurroyyan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The research aims to build Data Processing Applications at PT. Sumbawa Bamboo Propeller. This research uses mixed research methods, with the waterfall development method and is designed with a structured design. The system will be built using the PHP programming language with Codeigniter 3 using Visual Studio Code and Maria db as the database. This research succeeded in designing and building Data Processing Applications at PT. Sumbawa Bamboo Propeller and based on the results of the black box test which was tested directly by a senior with the title S. Kom stated that the Data Processing Application at PT. The Sumbawa Bamboo Baling has been successful and has been handed over to the Sumbawa bamboo propeller pt. The benefit that can be given from this research is that it can facilitate the employees of PT. Sumbawa Bamboo Baling in doing bookkeeping